Review of "A Regarded Self: Caribbean Womanhood and the Ethics of Disorderly Being" - Marietta Kosma (Ideas: Journal of English Literary Studies)
​This article reviews "A Regarded Self: Caribbean Womanhood and the Ethics of Disorderly Being," written by Kaiama L. Glover and published Duke University Press in 2021.